The development of a suspension spring in term of dimension - Mohd Fadhirul Amran, Jali @ Ali (2013)
This thesis involved with the development on the dimension of suspension spring. The parameter focused on was the wire diameter, (d). Suspension spring is very important for automotive industry as its functions are t give riding comfort, good stability and good control of the car. The objective of this thesis is to develop a new optimum dimension for wire diameter of a suspension spring. The technique used for developing the diameter was finite element analysis. The spring will be modeled using Solidworks and undergo static loading and cyclic loading which then will give the fatigue value. The wire diameter was changed within a range which is slightly different from the dimension of spring available in automotive market in Malaysia nowadays. An experiment was conducted which related with fatigue test. Specimens with the same material used for suspension spring was used. The fatigue test gives the data for S-N curves. From the cyclic loading, three methods were used, Morrow, Coffin-Manson, and Smith-Watson Topper method. The differences from the value obtained from these methods were compared. The load acting on the spring was exerted form the action of contact between the tire and the road. The results show the static failure, displacement, stress and the strain produced on the spring. The spring was analyzed until it is damaged which indicate the static failure value. Based on the analysis, the 12.5 mm wire diameter gives the optimum value which can have a longer fatigue life. The spring available in market was 13 mm and the value obtained from this thesis was slightly different from the market. The percentage of deviation was 3.8 %.